A carbon-coated aluminum foil, a method for preparing the same, and an application thereof
Patent Information
- Application Number
- CN202410563198.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]然而,将石墨烯类材料涂覆到铝基底上往往需要使用到粘接剂,行业内常用的粘接剂如丙烯酸类、聚偏氟乙烯类等并不具备导电性,这将直接导致涂炭铝箔的电阻增大,降低其充放电性能
[0024](1)本发明将涂炭浆料注入到狭缝容器中,干燥的过程中,利用氧化石墨烯表面基团在加热和潮湿环境下与铝箔基底发生界面键合生成了无需粘接剂的涂炭铝箔。降低了制备涂炭铝箔的生产成本,有效简化了工艺。
Smart Images

Figure CN122879698A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and more specifically to a carbon-coated aluminum foil, its preparation method, and its application. Background Technology
[0002] Aluminum foil is the most commonly used positive electrode current collector in the field of lithium-ion batteries. It can be used in conjunction with various positive electrode materials such as lithium manganese oxide, ternary materials, and lithium iron phosphate. However, conventional aluminum foil still has many drawbacks in actual use. For example, the inherent rigidity of aluminum foil limits its contact area with the positive electrode material, affecting the internal resistance of the positive electrode sheet; the adhesion strength between aluminum foil and adhesives and active materials is limited, affecting its service life; in addition, the oxidative decomposition products of the electrolyte undergo electrochemical reactions on the surface of the aluminum foil, which will accelerate the corrosion of the aluminum foil.
[0003] To address these issues, the surface of aluminum foil is typically modified when used as a positive current collector in industrial batteries. Among various modification methods, carbon coating of aluminum foil offers advantages such as low cost and significant performance improvement. Commonly used materials include carbon black, graphene, and carbon nanotubes. Compared to conventional aluminum foil, carbon-coated aluminum foil significantly improves battery internal resistance. Furthermore, extensive data shows that using carbon-coated aluminum foil in batteries results in lower self-discharge and a substantial increase in energy storage performance.
[0004] Among various carbon raw materials, graphene-based materials exhibit superior reinforcing effects compared to carbon black. Graphene possesses an extremely large specific surface area, thereby increasing the contact area between the active material and the positive current collector in the electrolyte. This allows for faster electron transfer and current collection during high-current rapid charging and discharging, improving the battery's rate charge / discharge performance. Furthermore, the electrical and thermal conductivity of regularly arranged graphene sheets on the surface of aluminum foil is far superior to that of ordinary carbon black coatings. Therefore, graphene shows great application potential in the field of carbon-coated aluminum foil.
[0005] However, coating graphene-based materials onto aluminum substrates often requires the use of adhesives. Commonly used adhesives in the industry, such as acrylic and polyvinylidene fluoride adhesives, are not conductive. This directly leads to increased resistance of the carbon-coated aluminum foil, reducing its charge-discharge performance. Furthermore, complex slurry formulations make it difficult to ensure the uniformity of graphene in the coating during mixing, increasing the risk of performance instability during use.
[0006] Therefore, in order to further reduce costs, decrease the resistance of carbon-coated aluminum foil, improve its thermal and electrical conductivity, and ensure the quality stability of carbon-coated aluminum foil in the industrial production process, it is necessary to develop a carbon-coated aluminum foil that does not require intermediate binders and has a simple preparation method. Summary of the Invention
[0007] To address the above problems, this invention provides a carbon-coated aluminum foil, its preparation method, and its application. The carbon-coated aluminum foil prepared by this invention does not require the use of an intermediate binder, and the preparation method is simple and easy to operate.
[0008] The first objective of this invention is to provide a method for preparing carbon-coated aluminum foil, comprising the following steps:
[0009] A carbon coating slurry with a pH less than 7 was prepared by dispersing graphene oxide in water.
[0010] A slotted container was prepared using aluminum foil as the raw material.
[0011] Carbon-coated aluminum foil is prepared by injecting carbon slurry into a slit container and then allowing interfacial bonding between graphene oxide and the aluminum foil substrate during the drying process.
[0012] In a further preferred embodiment of the present invention, the concentration of the carbon coating slurry is 0.5-18 mg / ml. For example, the concentration of the carbon coating slurry is 0.5 mg / ml, 1 mg / ml, 2 mg / ml, 3 mg / ml, 4 mg / ml, 5 mg / ml, 6 mg / ml, 7 mg / ml, 8 mg / ml, 9 mg / ml, 10 mg / ml, 11 mg / ml, 12 mg / ml, 13 mg / ml, 14 mg / ml, 15 mg / ml, 16 mg / ml, 17 mg / ml, or 18 mg / ml; however, it is not limited to the listed values, and other unlisted values within the above range are also applicable, which will not be elaborated here.
[0013] In a further preferred embodiment of the present invention, the concentration of the carbon coating slurry is 1.5 mg / ml.
[0014] In a further preferred embodiment of the present invention, the pH of the carbon coating slurry is 4-6. For example, pH is 4, 4.5, 5, 5.5, 6, or 6.5; however, it is not limited to the listed values, and other unlisted values within the above range are also applicable, which will not be elaborated here.
[0015] In a further preferred embodiment of the present invention, the aluminum foil is composed of aluminum foil A and aluminum foil B;
[0016] The slit container is prepared by sealing aluminum foil A to form a trough, and then covering the trough with aluminum foil B.
[0017] In a further preferred embodiment of the present invention, the height of the slit container is less than 3 mm. For example, the height can be 30 μm, 50 μm, 100 μm, 300 μm, 500 μm, 700 μm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, etc.; but it is not limited to the listed values, and other unlisted values within the above range are also applicable, which will not be described in detail here.
[0018] In a further preferred embodiment of the present invention, the drying temperature is 20-150℃ and the drying time is 2-12h.
[0019] For example, the drying temperatures are 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, and 150℃.
[0020] The drying time is 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h; however, it is not limited to the listed values. Other unlisted values within the above range are also applicable, and will not be elaborated here.
[0021] A second objective of this invention is to provide a carbon-coated aluminum foil prepared by the above-described preparation method.
[0022] A third objective of this invention is to provide the application of the aforementioned carbonized aluminum foil in lithium-ion batteries, specifically, the carbonized aluminum foil as a current collector.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) In this invention, carbon-coated slurry is injected into a slit container. During the drying process, the surface groups of graphene oxide undergo interfacial bonding with the aluminum foil substrate under heating and humid conditions to generate carbon-coated aluminum foil without the need for adhesives. This reduces the production cost of preparing carbon-coated aluminum foil and effectively simplifies the process.
[0025] (2) The present invention utilizes the primary hydrogen with high reducing power generated by the reaction of aluminum foil substrate with hot water and acidic solution; the reduction of primary hydrogen and the diffusion doping of Al element into the graphene oxide layer make the graphene oxide have good conductivity.
[0026] (3) The self-assembly of graphene oxide involves both evaporation-induced self-assembly and micro-region capillary-assisted self-assembly principles, resulting in a regular arrangement of graphene oxide, which improves the conductivity of the coating and makes the coating denser, thus enhancing its corrosion resistance. At the same time, the slit container made of aluminum plate changes the liquid bridge in the suspension during the drying process, which can effectively overcome the coffee ring effect in the solution drying process and make the coating more uniform. Attached Figure Description
[0027] Figure 1 This is a diagram showing the formation state of the carbon-coated aluminum foil prepared according to the present invention.
[0028] Figure 2 This is a schematic diagram illustrating the principle of preparing carbon-coated aluminum foil according to the present invention.
[0029] Figure 3 This is a scanned image of the cross-section of the carbon-coated aluminum foil prepared in Example 1;
[0030] Figure 4 The C1s spectrum of the carbon-coated aluminum foil prepared in Example 1;
[0031] Figure 5 The image shows the surface morphology of the carbon-coated aluminum foil prepared in Example 1.
[0032] Figure 6 Three-dimensional morphology image of the carbon-coated aluminum foil prepared in Example 1 under a laser confocal microscope.
[0033] Figure 7 The Tafel curve obtained by testing the carbon-coated aluminum foil prepared in Example 1 in 0.5M H2SO4 solution;
[0034] Figure 8 The Tafel curve is obtained by testing the carbon-coated aluminum foil prepared in Example 1 in 0.5M NaCl solution.
[0035] Figure 9 This is a scanned image of the cross-section of the carbon-coated aluminum foil prepared in Example 2;
[0036] Figure 10 The image shows the surface morphology of the carbon-coated aluminum foil prepared in Example 2.
[0037] Figure 11 The image shows the three-dimensional morphology of the surface of the carbon-coated aluminum foil prepared in Example 2.
[0038] Figure 12 The surface morphology of the carbon-coated aluminum foil prepared in Comparative Example 1 is shown.
[0039] Figure 13 The image shows the three-dimensional morphology of the carbon-coated aluminum foil surface prepared in Comparative Example 1.
[0040] Figure 14 The Tafel curve obtained by testing the carbon-coated aluminum foil prepared in Comparative Example 1 in 0.5M H2SO4 solution;
[0041] Figure 15 The Tafel curve obtained by testing the carbon-coated aluminum foil prepared in Comparative Example 1 in 0.5M NaCl solution;
[0042] Figure 16 The image shows the Tafel curve obtained by testing aluminum foil in 0.5M H2SO4 solution.
[0043] Figure 17 The image shows the Tafel curve obtained by testing aluminum foil in 0.5M NaCl solution. Detailed Implementation
[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] A method for preparing carbon-coated aluminum foil, characterized by comprising the following steps:
[0046] A carbon coating slurry was prepared by dispersing graphene oxide in water;
[0047] A slotted container was prepared using aluminum foil as the raw material.
[0048] Carbon-coated aluminum foil is prepared by injecting carbon slurry into a slit container and then allowing interfacial bonding between graphene oxide and the aluminum foil substrate during the drying process.
[0049] This invention involves injecting a carbon-coated slurry into a slit container. During the drying process, the reduction of graphene oxide utilizes primary hydrogen with high reducing power generated by the reaction of an aluminum foil substrate with hot water and an acidic solution. The reduction of primary hydrogen and the diffusion doping of Al elements into the graphene oxide layer give the graphene oxide excellent electrical conductivity. Figure 1 As shown, the self-assembly of graphene oxide in this invention involves both evaporation-induced self-assembly and micro-region capillary-assisted self-assembly principles, resulting in a regular arrangement of graphene oxide. This improves the conductivity of the coating while simultaneously making it denser and enhancing its corrosion resistance. During the drying reaction, the slit container made of aluminum plate alters the liquid bridges in the suspension, effectively overcoming the coffee ring effect during solution drying and ensuring a uniform coating.
[0050] In a preferred embodiment, the concentration of the carbon coating slurry is 0.5-18 mg / ml. If the concentration is too low, the graphene oxide may not completely cover the aluminum foil surface during assembly, resulting in severe defects on the carbon-coated aluminum foil surface. If the concentration is too high, due to the reduced solvent in the graphene oxide suspension, some graphene oxide flakes cannot be carried to the liquid bridge edge by the evaporated water vapor during the drying process in the slits to form a regularly arranged graphene coating, thus failing to form a highly regularly arranged reduced graphene oxide coating. A more detailed schematic diagram is shown below. Figure 2 As shown.
[0051] The pH value of the carbon coating slurry is less than 7. Aluminum foil readily reacts with H+ in acidic solutions. +The generation of primary H* with strong reducing properties is used to reduce graphene oxide in situ (although primary H* is easily generated in alkaline solutions and hot water, the graphene oxide prepared by the Hummers method is acidic or neutral, so there is no need to adjust the graphene oxide to alkaline, as this would increase the number of steps in the preparation process). However, excessive acidity can cause severe damage to the surface of the aluminum foil. Therefore, in order to ensure that the surface of the aluminum foil does not suffer damage that may affect the final performance of the material, while still generating enough primary H* to reduce graphene oxide, it is better to control the pH of the carbon coating slurry between 4 and 6.
[0052] It is understood that the graphene oxide used in this invention is prepared using a modified Hummers method, and the carbon coating slurry is a graphene oxide suspension. The oxidation time for preparing graphene oxide can be controlled, and the oxidation duration can roughly control the number of functional groups on the surface of graphene oxide, typically ranging from 0.5 h to 12 h.
[0053] It's important to note that a higher number of surface functional groups isn't always better; a moderate increase is beneficial. This is because more surface functional groups facilitate better interfacial bonding between graphene oxide and the aluminum foil surface, resulting in good interfacial adhesion even without a binder. However, when carbon-coated aluminum foil is used as the positive electrode current collector in a battery, the carbon layer also requires good conductivity and corrosion resistance. Too many functional groups can negatively impact the coating's conductivity, and the reduction of these functional groups can leave defects. Too many defects can reduce corrosion resistance. Therefore, a preferred time is typically 3-6 hours, which allows for the acquisition of sufficient functional groups while preventing the introduction of excessive defects.
[0054] It should be noted that the graphene oxide used in this invention is prepared using a strong acid solution, so the graphene oxide suspension obtained by directly dispersing it in water is an acidic solution.
[0055] It is understandable that graphene oxide prepared using conventional methods can also be used for preparation. If the pH of the graphene oxide solution does not meet the requirements for experimental preparation, an acidic adjuster (such as 0.1 mol / L sulfuric acid) can be used to adjust the graphene oxide solution to acidity (such as pH = 1, 2, 3, 4, 5 or 6) before use. However, this will increase the number of steps in the preparation process.
[0056] In a preferred embodiment, the injection volume of the carbon coating slurry is 0.01-1 ml / cm². 2 The amount of carbon-coated slurry injected should be equal to the internal volume of the slit container. Graphene assembly is controlled by changing the contact angle of the graphene solution between the two aluminum foil layers. The volume of the slit container can be determined based on actual conditions.
[0057] In a preferred embodiment, the aluminum foil is composed of aluminum foil A and aluminum foil B;
[0058] A slotted container is prepared by sealing aluminum foil A to form a tank, and then covering the tank with aluminum foil B. The slotted container should have tiny capillary slits around its perimeter to serve as channels for moisture evaporation.
[0059] It should be noted that aluminum foil needs to be sanded before use. The sandpaper used should have a roughness of 3000 grit or higher. Sanding should be done by alternating between horizontal and vertical sanding, and the surface oxide layer should be completely removed.
[0060] When performing edge sealing, use adhesive tape to seal the edges of the aluminum foil. The tape should adhere tightly to the substrate to prevent the carbon coating paste from overflowing. The tape used for edge sealing should have stable properties up to 150°C. Adhesive tapes include, but are not limited to, KAPTON tape. It is understood that the size and depth of the internal space can be adjusted as needed during edge sealing.
[0061] In a preferred embodiment, the height between aluminum foil A and aluminum foil B is less than 3 mm, providing micro-capillary pressure for the carbon coating slurry to react in the slit.
[0062] In a preferred embodiment, the drying temperature is 20-150°C and the drying time is 2-12 hours.
[0063] The carbon-coated aluminum foil prepared by this invention can be used in lithium-ion batteries, specifically as a current collector.
[0064] The performance of the carbon-coated aluminum foil prepared by this invention was evaluated according to the following aspects:
[0065] (1) Carbon layer thickness test: The cross section was observed using a scanning electron microscope to measure the coating thickness.
[0066] (2) Conductivity test: The conductivity of the carbon-coated aluminum foil surface was tested using a four-point probe.
[0067] (3) Interfacial chemical bond test: X-ray photoelectron spectroscopy was used to measure the interfacial bonding.
[0068] (4) Interface bonding strength test: The bonding strength between the carbon layer and the aluminum foil was tested using a scratch tester. During the test, a 0.2 mm diamond tip indenter was used to pull the graphene-coated sample at a constant speed of 0.1 mm / s, applying a progressive load of 1 N to 30 N.
[0069] (5) Surface morphology of carbon-coated aluminum foil: The surface morphology of the carbon layer was observed using scanning electron microscopy.
[0070] (6) Surface uniformity test: The surface roughness of the carbon-coated aluminum foil was tested using a laser confocal microscope.
[0071] (7) Corrosion Resistance Test: The corrosion resistance of carbonized aluminum foil in 0.5M H2SO4 solution and 0.5M NaCl solution was tested using a Chenhua electrochemical workstation. A three-electrode system was used in the experiment, with a graphite rod as the counter electrode and a double-section Ag|AgCl as the reference electrode. Tafel polarization curves were generated by applying a potential to the reference electrode at a scan rate of 5mV / s, and the corrosion potential and corrosion current density during the corrosion process were obtained.
[0072] The present invention is further illustrated by the following examples:
[0073] Example 1
[0074] Preparation of an adhesive-free carbon-coated aluminum foil for lithium batteries:
[0075] Step 1: Graphene oxide is prepared using the modified Hummers method. The preparation steps are as follows:
[0076] Measure 96 mL of 84% concentrated sulfuric acid into a dry beaker. Place the beaker in a water bath at a temperature below 20°C and slowly add 3 g of graphite powder over 35 minutes with magnetic stirring to ensure uniform mixing. Then slowly add 10.5 g of potassium permanganate over 100 minutes. After the addition is complete, continue the reaction for 40 minutes, followed by sonication for 4 hours.
[0077] Next, slowly add 138 mL of deionized water while stirring, and react for 15 min. Then add 360 mL of 90℃ deionized water to dilute, and while stirring, add 30 mL of 30% hydrogen peroxide solution to treat the remaining potassium permanganate in the mixture. Centrifuge while hot.
[0078] The precipitate was first washed with 5% hydrochloric acid, then washed five times with deionized water until the supernatant was neutral, and finally freeze-dried to obtain graphene oxide.
[0079] Step 2: Prepare a 1.5 mg / ml graphene oxide suspension to form a carbon coating slurry with a pH of 5. Use 3000-grit sandpaper to prepare a 20×30 cm slurry. 2 The surface of the aluminum foil was polished to remove the oxide layer. The aluminum foil surface was then sealed with KAPTON tape to a height of 100 μm. Another piece of aluminum foil of the same size was then placed on top to form a slit container. The prepared carbon-coated slurry was injected into the capillary slits, the injection volume equal to the internal volume of the slit container. The container was then dried in a sealed oven at 120°C for 4 hours. After drying, the two layers of aluminum foil were separated to obtain the carbon-coated aluminum foil.
[0080] The performance test results of the carbon-coated aluminum foil in Example 1 are as follows:
[0081] In conventional carbon-coated aluminum foil, a large thickness means using more adhesive to adhere the coating and prevent the carbon layer from expanding and detaching during operation. The addition of adhesive reduces conductivity, thus affecting battery performance. In this invention, no adhesive is used; chemical bonding is achieved through interfacial chemical reactions. However, if the assembled graphene coating thickness exceeds 2 μm (a thickness of 0.2-2 μm is generally considered optimal for carbon-coated aluminum foil; excessive thickness increases the overall volume, reduces conductivity, and increases cost), Al cannot diffuse to the far ends of the coating to form chemical connections. Since graphene layers are connected by van der Waals forces, a thick coating carries the risk of surface graphene expanding and peeling off during operation. Furthermore, although this method achieves in-situ reduction of graphene oxide on the aluminum foil surface, this reduction mechanism consumes a small amount of aluminum foil surface area; a large thickness hinders reduction and affects the conductivity of the carbon-coated aluminum foil. The carbon layer thickness on the surface of the carbon-coated aluminum foil in this invention is approximately 600 nm. Figure 3 This is beneficial for improving the conductivity of carbon-coated aluminum foil.
[0082] The conductivity of the carbon-coated aluminum foil prepared in Example 1 was measured to be 1423 S / m. The high conductivity of the carbon-coated aluminum foil can effectively reduce the internal resistance of the battery, improve battery performance, and extend battery life.
[0083] Figure 4 The C1s spectrum of the carbon-coated aluminum foil prepared in Example 1 shows that the content of reinforcing CO-Al bonds is 10.81%. Furthermore, the interfacial bonding strength between the carbon layer and the aluminum foil was tested and found to be 8.5 N / m. Improved interfacial bonding strength is beneficial for extending the service life of the carbon-coated aluminum foil and preventing the carbon layer from peeling off during use.
[0084] A uniform surface can provide a stable contact area between the active material and the positive electrode current collector in the electrolyte, thereby enabling faster electron transfer and collection during high-current rapid charging and discharging, and improving the battery's rate charge and discharge performance. Figure 5 The image shows the surface morphology of the carbon-coated aluminum foil prepared in Example 1. It can be seen that the surface has a uniform and fine wrinkled structure, which is beneficial to increasing the contact area between the active material in the electrolyte and the positive electrode current collector. This allows for faster electron transfer and current collection during high-current fast charging and discharging, thereby improving the battery's rate charge and discharge performance and helping lithium batteries improve their efficiency and adapt to high-rate fast charging.
[0085] Figure 6The image shows the three-dimensional morphology of the carbon-coated aluminum foil prepared in Example 1 under a laser confocal microscope. The results show that the surface roughness of the carbon-coated aluminum foil is 233 nm.
[0086] Figure 7 The Tafel curves obtained by testing the carbon-coated aluminum foil prepared in Example 1 in 0.5M H2SO4 solution show a corrosion potential of -541mV and a corrosion current density of 6.52×10⁻⁶. -7 A / cm 2 .
[0087] Figure 8 The Tafel curves obtained by testing the carbon-coated aluminum foil prepared in Example 1 in 0.5M NaCl solution show that the corrosion potential is -744mV and the corrosion current density is 3.85×10⁻⁶ mV. -8 A / cm 2 This indicates that the carbon-coated aluminum foil has excellent corrosion resistance.
[0088] Example 2
[0089] Preparation of an adhesive-free carbon-coated aluminum foil for lithium batteries:
[0090] Step 1: Graphene oxide is prepared using the modified Hummers method. The preparation steps are as follows:
[0091] Measure 96 mL of 84% concentrated sulfuric acid into a dry beaker. Place the beaker in a water bath at a temperature below 20°C and slowly add 3 g of graphite powder over 35 minutes with magnetic stirring to ensure uniform mixing. Then slowly add 10.5 g of potassium permanganate over 100 minutes. After the addition is complete, continue the reaction for 40 minutes, followed by sonication for 6 hours.
[0092] Next, slowly add 138 mL of deionized water while stirring, and react for 15 min. Then add 360 mL of 90℃ deionized water to dilute, and while stirring, add 30 mL of 30% hydrogen peroxide solution to treat the remaining potassium permanganate in the mixture. Centrifuge while hot.
[0093] The precipitate was first washed with 5% hydrochloric acid, then washed several times with deionized water to bring the pH of the supernatant to around 6, and finally vacuum dried to obtain graphene oxide.
[0094] Step 2: Prepare a 1 mg / ml graphene oxide suspension to form a carbon coating slurry with a pH of 6. Use 7000-grit sandpaper to prepare a 20×30cm slurry. 2The surface of the aluminum foil was polished to remove the oxide layer. The aluminum foil surface was then sealed with BOPP tape to a height of 30 μm. Another piece of aluminum foil of the same size was then placed on top to form a slit container. The prepared carbon-coated slurry was injected into the capillary slits, the injection volume equal to the internal volume of the slit container. The container was then dried in a sealed oven at 70°C for 6 hours. After drying, the two layers of aluminum foil were separated to obtain the carbon-coated aluminum foil.
[0095] The performance test results of the carbon-coated aluminum foil in Example 2 are as follows:
[0096] Figure 9 This is a scanned image of the cross-section of the carbon-coated aluminum foil prepared in Example 2. Figure 9 It can be seen that the carbon layer thickness of the carbon-coated aluminum foil is approximately 150 nm. Tests show that the conductivity of the carbon-coated aluminum foil is 956 S / m.
[0097] By testing the bonding strength between the carbon layer and the aluminum foil, it was found that the interfacial bonding strength was 13.7 N / m.
[0098] Figure 10 The surface morphology of the carbon-coated aluminum foil prepared in Example 2 shows that the surface has a uniform and fine wrinkled structure, and the increased surface area is beneficial for its application in lithium-ion batteries.
[0099] Figure 11 The three-dimensional morphology of the carbon-coated aluminum foil surface prepared in Example 2 has a surface roughness of 98 nm. This is because the graphene film is very thin and therefore grows in close contact with the aluminum foil substrate.
[0100] Example 3
[0101] Preparation of an adhesive-free carbon-coated aluminum foil for lithium batteries:
[0102] Step 1: Graphene oxide is prepared using the modified Hummers method. The preparation steps are as follows:
[0103] Measure 96 mL of 84% concentrated sulfuric acid into a dry beaker. Place the beaker in a water bath at a temperature below 20°C and slowly add 3 g of graphite powder over 35 minutes with magnetic stirring to ensure uniform mixing. Then slowly add 10.5 g of potassium permanganate over 100 minutes. After the addition is complete, continue the reaction for 40 minutes, followed by sonication for 4 hours.
[0104] Next, slowly add 138 mL of deionized water while stirring, and react for 15 min. Then add 360 mL of 90℃ deionized water to dilute, and while stirring, add 30 mL of 30% hydrogen peroxide solution to treat the remaining potassium permanganate in the mixture. Centrifuge while hot.
[0105] The precipitate was first washed with 5% hydrochloric acid, then washed five times with deionized water until the supernatant was neutral, and finally freeze-dried to obtain graphene oxide.
[0106] Step 2: Prepare a 0.5 mg / ml graphene oxide suspension to form a carbon coating slurry with a pH of 5. Use 3000-grit sandpaper to prepare a 20×30 cm slurry. 2 The surface of the aluminum foil was polished to remove the oxide layer. The edges of the aluminum foil were then sealed with KAPTON tape to a height of 1 mm. Another piece of aluminum foil of the same size was then placed on top to form a slit container. The prepared carbon-coated slurry was injected into the capillary slits, the amount of slurry equal to the internal volume of the slit container. The container was then dried in a sealed oven at 20°C for 12 hours. After drying, the two layers of aluminum foil were separated to obtain the carbon-coated aluminum foil.
[0107] Example 4
[0108] Preparation of an adhesive-free carbon-coated aluminum foil for lithium batteries:
[0109] Step 1: Graphene oxide is prepared using the modified Hummers method. The preparation steps are as follows:
[0110] Measure 96 mL of 84% concentrated sulfuric acid into a dry beaker. Place the beaker in a water bath at a temperature below 20°C and slowly add 3 g of graphite powder over 35 minutes with magnetic stirring to ensure uniform mixing. Then slowly add 10.5 g of potassium permanganate over 100 minutes. After the addition is complete, continue the reaction for 40 minutes, followed by sonication for 4 hours.
[0111] Next, slowly add 138 mL of deionized water while stirring, and react for 15 min. Then add 360 mL of 90℃ deionized water to dilute, and while stirring, add 30 mL of 30% hydrogen peroxide solution to treat the remaining potassium permanganate in the mixture. Centrifuge while hot.
[0112] The precipitate was first washed with 5% hydrochloric acid, then washed five times with deionized water until the supernatant was neutral, and finally freeze-dried to obtain graphene oxide.
[0113] Step 2: Prepare a graphene oxide suspension at a concentration of 18 mg / ml to form a carbon coating slurry with a pH of 6. Use 3000-grit sandpaper to prepare a 20×30cm slurry. 2The surface of the aluminum foil is polished to remove the oxide layer. The edges of the aluminum foil are then sealed with KAPTON tape to a height of 2mm. Another piece of aluminum foil of the same size is then placed on top to form a slit container. The prepared carbon-coated slurry is injected into the capillary slits, the amount of slurry equal to the internal volume of the slit container. The container is then dried in a sealed oven at 150°C for 2 hours. After drying, the two layers of aluminum foil are separated to obtain the carbon-coated aluminum foil.
[0114] Example 5
[0115] Preparation of an adhesive-free carbon-coated aluminum foil for lithium batteries:
[0116] Step 1: Graphene oxide is prepared using the modified Hummers method. The preparation steps are as follows:
[0117] Measure 96 mL of 84% concentrated sulfuric acid into a dry beaker. Place the beaker in a water bath at a temperature below 20°C and slowly add 3 g of graphite powder over 35 minutes with magnetic stirring to ensure uniform mixing. Then slowly add 10.5 g of potassium permanganate over 100 minutes. After the addition is complete, continue the reaction for 40 minutes, followed by sonication for 4 hours.
[0118] Next, slowly add 138 mL of deionized water while stirring, and react for 15 min. Then add 360 mL of 90℃ deionized water to dilute, and while stirring, add 30 mL of 30% hydrogen peroxide solution to treat the remaining potassium permanganate in the mixture. Centrifuge while hot.
[0119] The precipitate was first washed with 5% hydrochloric acid, then washed five times with deionized water until the supernatant was neutral, and finally freeze-dried to obtain graphene oxide.
[0120] Step 2: Prepare a 10 mg / ml graphene oxide suspension to form a carbon coating slurry with a pH of 6. Use 3000-grit sandpaper to prepare a 20×30 cm... 2 The surface of the aluminum foil was polished to remove the oxide layer. The edges of the aluminum foil were then sealed with KAPTON tape to a height of 2.5 mm. Another piece of aluminum foil of the same size was then placed on top to form a slit container. The prepared carbon-coated slurry was injected into the capillary slits, the amount of slurry equal to the internal volume of the slit container. The container was then dried in a sealed oven at 130°C for 5 hours. After drying, the two layers of aluminum foil were separated to obtain the carbon-coated aluminum foil.
[0121] Comparative Example 1
[0122] This comparative example provides a carbon-coated aluminum foil prepared by a conventional coating method:
[0123] Step 1: Graphene oxide is prepared using the modified Hummers method. The preparation steps are as follows:
[0124] Measure 96 mL of 84% concentrated sulfuric acid into a dry beaker. Place the beaker in a water bath at a temperature below 20°C and slowly add 3 g of graphite powder over 35 minutes with magnetic stirring to ensure uniform mixing. Then slowly add 10.5 g of potassium permanganate over 100 minutes. After the addition is complete, continue the reaction for 40 minutes, followed by sonication for 4 hours.
[0125] Next, slowly add 138 mL of deionized water while stirring, and react for 15 min. Then add 360 mL of 90℃ deionized water to dilute, and while stirring, add 30 mL of 30% hydrogen peroxide solution to treat the remaining potassium permanganate in the mixture. Centrifuge while hot.
[0126] The precipitate was first washed with 5% hydrochloric acid, then washed five times with deionized water until the supernatant was neutral, and finally freeze-dried to obtain graphene oxide.
[0127] Step 2: Prepare a 1.5 mg / ml graphene oxide suspension to form a carbon coating slurry with a pH of 5. Use 3000-grit sandpaper to prepare a 20×30 cm slurry. 2 The aluminum foil surface was polished to remove the oxide layer. A graphene oxide solution was then directly coated onto the aluminum foil surface using a conventional coating method, with the same amount of graphene oxide solution applied as in Example 1. The foil was dried in a sealed oven at 120°C for 4 hours to obtain carbon-coated aluminum foil.
[0128] The performance test results of the carbon-coated aluminum foil in Comparative Example 1 are as follows:
[0129] Figure 12 The surface morphology of the carbon-coated aluminum foil prepared for Comparative Example 1 is shown. The surface is uneven with significant undulations, which prevents graphene from being fully deposited in some areas. Furthermore, the large undulations indicate instability during operation, and areas with significant graphene accumulation risk detachment. The electrical conductivity of the carbon-coated aluminum foil is 0.75 S / m. Graphene oxide is almost insulating without reduction, and the surface graphene is virtually impossible to reduce under this coating method.
[0130] By testing the bonding strength between the carbon layer and the aluminum foil, it was found that the interfacial bonding strength is 1.3 N / m.
[0131] The surface roughness of the carbon-coated aluminum foil is 927 nm. Its three-dimensional morphology is as follows: Figure 13As shown, during the evaporation of the solution, the solute undergoes thermal convection within the droplets, resulting in significant solute segregation and a highly uneven graphene layer. Measuring its thickness under these conditions is unreasonable; therefore, the coating thickness was not measured using scanning electron microscopy in the comparative examples.
[0132] Figure 14 The Tafel curves obtained by testing the carbon-coated aluminum foil prepared in Comparative Example 1 in 0.5 M H2SO4 solution show that the corrosion potential is -573 mV and the corrosion current density is 3.04 × 10⁻⁶ mV. -5 A / cm 2 .
[0133] Figure 15 The Tafel curves obtained by testing the carbon-coated aluminum foil prepared for comparison in 0.5M NaCl solution show that the corrosion potential is -643mV and the corrosion current density is 4.02×10⁻⁶. -5 A / cm 2 .
[0134] Electrochemical corrosion performance is typically evaluated by the magnitude of corrosion potential and corrosion current density. When evaluating a material's corrosion resistance, the primary parameter is corrosion current density; the lower the corrosion current density, the better the material's corrosion resistance, because the corrosion current is caused by the dissolution of the material. Corrosion potential is only a parameter to consider when the corrosion currents of two materials are roughly the same; the higher the corrosion potential, the better the material's corrosion resistance (proneness). Comparing Example 1 and Comparative Example 1, it can be seen that the carbon-coated aluminum foil prepared according to this invention exhibits excellent corrosion resistance.
[0135] The electrical conductivity of pure aluminum is 37.7 × 10⁻⁶. 6 S / m, this figure is far higher than that of any carbon-coated aluminum foil. However, aluminum foil has a certain rigidity, and the contact area with the positive electrode material in the electrode sheet is limited, affecting the internal resistance of the positive electrode sheet. Furthermore, batteries such as lithium iron phosphate have poor conductivity, lacking a bridge for electron transport between them and the plain aluminum foil. Therefore, after carbon coating the surface of the aluminum foil, the carbon coating layer can act as a bridge, tightly bonding the positive electrode active material to the aluminum foil, with particles interlocking, thereby improving the conductivity of the positive electrode sheet.
[0136] The inventors further measured the corrosion resistance of pure aluminum foil and obtained the corrosion potential and corrosion current density during the corrosion process.
[0137] Figure 16 The Tafel curves obtained from testing aluminum foil in 0.5M H₂SO₄ solution show a corrosion potential of -688mV and a corrosion current density of 1.25×10⁻⁶. -4 A / cm2 . Figure 17 The Tafel curves obtained from testing aluminum foil in 0.5M NaCl solution show a corrosion potential of -700mV and a corrosion current density of 1.29 × 10⁻⁶ mV. -6 A / cm 2 It can be seen that carbon coating on the surface of aluminum foil effectively improves its corrosion resistance.
[0138] In summary, the preparation method of the present invention can still uniformly coat the aluminum foil even at low thickness, resulting in an excellent surface structure. The prepared carbon-coated aluminum foil has a certain interfacial bonding strength, high conductivity, and better corrosion resistance than pure aluminum.
[0139] Table 1 of the paper "Research Progress on Functional Modification of Lithium-ion Battery Current Collectors" published by Jia Yafeng et al. in *New Materials Industry* records that the coating thickness of commercially available carbon-coated aluminum foil current collectors is 0.6-2.0 μm on both sides. The carbon-coated aluminum foil prepared in this invention has a single carbon layer thickness of 150-600 nm and a conductivity of 956-1423 S / m, which meets the requirements for application in lithium-ion batteries. This invention is simple to operate, requires no intermediate binder, and the prepared carbon-coated aluminum foil has excellent application potential in lithium-ion batteries.
[0140] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.
[0141] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A method for preparing carbon-coated aluminum foil, characterized in that, Includes the following steps: A carbon coating slurry with a pH less than 7 was prepared by dispersing graphene oxide in water. A slotted container was prepared using aluminum foil as the raw material. Carbon-coated aluminum foil is prepared by injecting carbon slurry into a slit container and then allowing interfacial bonding between graphene oxide and the aluminum foil substrate during the drying process.
2. The method for preparing carbon-coated aluminum foil according to claim 1, characterized in that, The concentration of the carbon coating slurry is 0.5-18 mg / ml.
3. The method for preparing carbon-coated aluminum foil according to claim 2, characterized in that, The concentration of the carbon coating slurry is 1.5 mg / ml.
4. The method for preparing carbon-coated aluminum foil according to claim 1, characterized in that, The pH of the carbon coating slurry is 4-6.
5. The method for preparing carbon-coated aluminum foil according to claim 1, characterized in that, Aluminum foil consists of aluminum foil A and aluminum foil B; The slit container is prepared by sealing aluminum foil A to form a trough, and then covering the trough with aluminum foil B.
6. The method for preparing carbon-coated aluminum foil according to claim 1, characterized in that, The height of the slit container is less than 3mm.
7. The method for preparing carbon-coated aluminum foil according to claim 1, characterized in that, The drying temperature is 20-150℃, and the drying time is 2-12h.
8. A carbon-coated aluminum foil prepared by the preparation method according to any one of claims 1-7.
9. The application of the carbon-coated aluminum foil according to claim 8 in a lithium-ion battery.
10. The application of the carbon-coated aluminum foil according to claim 9 in a lithium-ion battery, characterized in that, Carbon-coated aluminum foil is used as a current collector.